2018
DOI: 10.1111/jcms.12688
|View full text |Cite
|
Sign up to set email alerts
|

The Alleged Opposition Deficit in European Union Politics: Myth or Reality?

Abstract: According to the ‘opposition deficit thesis’ European Union politics is characterized by a conspicuous absence of opposition to the policies promoted by the EU. However, once we start looking for systematic evidence supporting the claim of an opposition deficit in EU politics, we come up surprisingly empty handed. This article seeks to rectify the lacuna in previous research by examining how much and what type of opposition actually exist in EU politics. The study formulates four hypotheses on the state of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Furthermore, the current examination improves our understanding of the role that Eurosceptic parties play in EU affairs, by corroborating some results from previous research. In a case study of Sweden, Karlsson and Persson () found a strong dominance of hard Eurosceptic parties when it came to opposition in polity matters, whereas the share of policy opposition was much more evenly distributed between Eurosceptics and mainstream parties. These key results are confirmed by our comparative analysis of opposition in the Danish and Swedish EACs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the current examination improves our understanding of the role that Eurosceptic parties play in EU affairs, by corroborating some results from previous research. In a case study of Sweden, Karlsson and Persson () found a strong dominance of hard Eurosceptic parties when it came to opposition in polity matters, whereas the share of policy opposition was much more evenly distributed between Eurosceptics and mainstream parties. These key results are confirmed by our comparative analysis of opposition in the Danish and Swedish EACs.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, political opposition in EU politics has been considered a scarce commodity. This alleged ‘opposition deficit’ (Karlsson & Persson ) is considered to result from a situation where the EU has helped ‘to depoliticize decision‐making at the national level, tending therefore to transform member states to polities without politics’ (Mair , 8). Deprived of alternatives and choice in EU politics, citizens have started to increasingly support parties that oppose the EU political system as such; the absence of policy opposition has thus produced a breeding ground for Euroscepticism and electoral success for Eurosceptic challenger parties (Mair , 139–40).…”
Section: Previous Research On Eurosceptic Oppositionmentioning
confidence: 99%
“…However, opposition is not only about delivering critique it is also, crucially, about presenting alternatives and this key dimension of opposition is not addressed by Hoerner. In another recent article Karlsson and Persson (2018) do address opposition in the form of critique as well as presenting alternatives. Their results imply there exists more opposition in EU politics than what has often been assumed, but since this is a case study of only one member state (Sweden) it fails to provide a general picture of opposition in EU politics.…”
Section: Political Oppositionsurvey Of the Fieldmentioning
confidence: 99%
“…A second general theme we can derive from the scholarly literature and that can function as a starting point for our empirical enquiry is the difference between NPs of EU member states in how these representative bodies monitor the progress in EU legislative processes (Karlsson & Persson, 2018;Raunio & Hix, 2000;Winzen, 2012). First, the scope of information rights varies greatly between parliaments, with some having only weak, informal or incomplete access to EU documents, parliaments receiving all legislative proposals that fall within their remit of responsibility, and other parliaments with rights to hold hearings and access additional background material (Winzen, 2012).…”
Section: State Of the Art: Nps And Triloguesmentioning
confidence: 99%
“…As a result, NPs were often labelled as 'victims' or 'latecomers' to the European integration process (Auel & Benz, 2005;O'Brennan & Raunio, 2007;Raunio, 2011). The discrepancy between the need for parliamentary control at the national level and the inability of NPs to control the national executive branch in the complex EU legislative process seriously undermines the legitimacy of the representative democratic system in Europe, with de-parliamentarization as a result (Maurer & Wessels, 2001; but see Karlsson & Persson, 2018).…”
Section: Introductionmentioning
confidence: 99%